Solvent Engineering of Ionic Liquids for Stable and Efficient Perovskite Solar Cells. Issue 1 (8th November 2022) - Wang, Fei; Zhou, Xianfang; Liang, Xiao; Duan, Dawei; Ge, Chuang-Ye; Lin, Haoran; Zhu, Quanyao; Li, Liang; Hu, Hanlin
Abstract : Solution‐processed perovskite solar cells (PSCs) are widely and dramatically developed with certificated record efficiency up to 25.7%, which have been regarded as the most promising candidates for next‐generation photovoltaic devices. However, the current decent devices are dominantly fabricated based on traditional toxic organic solvents such as N, N ‐dimethylformamide and dimethyl sulfoxide, which inevitably leads to environmental damage and potential safety accidents. As green and nontoxic molten salts at room temperature, ionic liquids (ILs) as promising alternatives for traditional toxic organic solvents have attracted intensive research interest worldwide in the field of perovskite photovoltaics with encouraging development.  Herein, especially concentrating on ILs solvent engineering rather than additive or post‐treatment, discussion and summarization upon the recent progress on perovskite photovoltaics including both 3D and 2D‐based PSCs is systematically carried out. An in‐depth understanding regarding the interactions between IL molecules and perovskite precursor materials is thoroughly explored and summarized. Moreover, the detailed influence of ILs as solvent(s) on the aspects of perovskite material crystallization regulation, surface defect passivation, and performance improvement of resultant device is comprehensively overviewed and discussed. Finally, prospects of the application of ILs in the PSCs through solvent engineering are provided for further developments. Abstract : This study provides an overview, classification, and applications of ionic liquids (ILs) as pure processing solvents in perovskite photovoltaics. The use and role of ILs as pure solvents in the perovskite precursor solution, as well as the impact on the stability and photovoltaic performance are summarized.